(untitled) (Comprehensive Journal of Science, 2026)
This research presents a system that utilizes Internet of Things (IoT) technology in conjunction with the NeuroSky MindWave device, Bluetooth, GSM, and Global Positioning System (GPS) to remotely monitor epilepsy patients. The NeuroSky MindWave device is used as a measuring device for brainwave signals and detecting abnormal activity patterns associated with seizures. The data is wirelessly transmitted to an IoT gateway device using Bluetooth technology. The IoT gateway device serves as a central hub that collects the brainwave data from the NeuroSky MindWave device and sends it to a cloud-based server using GSM technology. The cloud-based server processes the data using advanced analysis algorithms to identify seizure patterns and contributing factors. In addition to the brainwave data, the system incorporates GPS technology to track the patient’s location in real-time. This information is transmitted along with the brainwave data to the cloud-based server, enabling accurate documentation of seizure occurrences and their geographical locations. Caregivers and healthcare professionals can access the cloud-based server through a web or mobile application, which provides a user-friendly interface for visualizing the brainwave data, monitoring the patient’s location, setting up personalized seizure detection alerts, and managing medication reminders. When abnormal brain activity indicative of a seizure is detected, the system triggers an alert through the mobile application and sends an SMS notification to designated caregivers or emergency services. This prompt response allows for immediate assistance and intervention, potentially reducing the severity and duration of seizures. The proposed system aims to improve the quality of life for epilepsy patients, enhance seizure management, and facilitate timely medical interventions.